The Effect Of Csr; Credit Interest; And Bank Size On Financial Performance. - Bangun, Nurainun (Jurnal Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effect of corporate social responsibility, credit interest, and bank size on financial performance at banking companies listed in Indonesia Stock Exchange in 2015-2017. The benefit of this research is to help convince investors to invest in the bank's companies . This research used a purposive sampling technique to collect data and consisted of 93 banking companies listed on the Indonesia Stock Exchange in 2015-2017. The statistical method used in this research is used multiple linear regression analysis methods. In this research used the Eviews program, 10 version. The results of the research based on the tests that have been carried out state that corporate social responsibility, and credit interest not had a significant effect on financial performance, while bank size had a significant positive effect on financial performance.